A case of abdominal tuberculosis: a challenging diagnosis - Thirupathi, Siraveni; P., Chinnaiyan; Chandrababu, Sujeetha (International Journal of Research in Medical Sciences, 2019)
Tuberculosis continues to intimidate the human race since traditional for an extremely long time not only due to its effects as a medical ailment, but also it impacts as a social and economic burden. Tuberculosis is a major health problem in developing countries. Abdominal tuberculosis is most common extra pulmonary tuberculosis. Tuberculosis can suspect in endemic countries like India, and can have various presentations and complications, it can mislead the diagnosis. Here, this case it involves small bowel, large bowel and peritoneum with different presentation.